AB0915 Spondyloepiphyseal Dysplasia: About 7 Cases and a Review of the Literature. (9th June 2015) - Aouadi, A.; Rekik, S.; Boussaid, S.; Ajleni, H.; Sahli, H.; Cheour, E.; Elleuch, M.
Abstract : Background: Spondyloepiphyseal dysplasia (DSE) is a genetic chondrodysplasia causing early osteoarthritis witch prédominates in hips, knees and shoulders. We report in this context 7cases. Objectives: We propose to study the clinical and radiologcal features of spondyloepiphyseal dysplasia in our patients. Methods: We studied the clinical and radiological features collected from records of patients treated for spondyloepiphyseal dysplasia. Results: This was 7 patients (4H/3F) 31. Their middle age was 31, 5 years. The diagnosis delay was on average 6, 25ans [4 months-13 years]. Clinical signs were present in all cases: low back pain in 3 cases, hip disease in 3 cases, and a dwarfism in 2 cases. The clinical examination objectified abnormalities in all patients. This was strain in six cases: flexion of the elbows and/or knees, scoliosis in 3 cases each. Joint restriction in one or both hips was observed in 2 patients. The diagnosis was retained in all patients on radiological data. Vertebral dysplasia was demonstrated in 4cas. Femoral involvement was noted in 2 cases (pseudo rheumatoid dysplasia), knees in 2 cases. Three patients underwent measurement of bone mineral density, which found osteoporosis. Treatment was to prescribe analgesics and nonsteroidal antiinflammatory for all patients, a support unit in rehabilitation and physical medicine in one case and total hip in one case. Conclusions: SDE is a child or adolescent pathology which must always be suspected in advanced osteoarthritis in young adults. Early diagnosis, through a better understanding of this entity, could improve the quality of life of these patients. References: Kohler G, Hesse B. Epiphyseal dysplasia–symptoms and differential diagnostic aspects. Z Orthop Ihre Grenzgeb. 2004 Jul-Aug;142(4):397-402. Acknowledgements: SDE. Disclosure of Interest: None declared